Identification of an Exosome-relevant SNHG6-hsa-miR-429- CHRDL1/CCNA2 Axis for Lung Adenocarcinoma Prognosis Evaluation - Yuan, Yuan; Li, Qian; Chen, Feifei; Zhao, Yujie; Ma, Jiyong; Fang, Surong (Current Medicinal Chemistry, 2024)
Aim: To explore an exosome-relevant molecular classification in lung adenocarcinoma (LUAD). Background: Exosome genes or relevant non-coding RNAs are regulators of cancer treatment and prognosis, but their function in LUAD has not yet been determined. Objective: Unraveling a molecular classification applying exosome-related RNA networks for LUAD prognosis evaluation. Methods: MicroRNA sequencing data (miRNAs-seq) and RNA sequencing data (RNA- seq) were derived from The Cancer Genome Atlas (TCGA). The ConsensusCluster- Plus package was used for molecular typing in LUAD based on 121 Exosome-related genes. Then, a limma package was conducted to explore differentially expressed mRNAs (DEmRNAs), differentially expressed miRNAs (DEmiRNAs) and differentially expressed lncRNAs (DElncRNAs) in molecular typing for constructing an Exosome-driven competing endogenous RNA network (ceRNA). Dominant miRNAs, as well as target mRNAs, were identified by COX modeling and Kaplan-Meier survival analysis. Results: Two Exosome-associated molecular clusters classified in LUAD. The C2 cluster favored high clinicopathology and showed a trend toward poor prognosis. 29 lncRNA- miRNA and 12 miRNA-mRNA interaction pairs were identified. The hsa-miR-429 was the pivotal miRNA in the network that affected the prognosis of LUAD. According to the interaction relationship and LUAD prognostic role, SNHG6-hsa- miR-429-CHRDL1/CCNA2 was identified. SNHG6-hsa-miR-429-CHRDL1 exerts oncogenic effects, and SNHG6-hsa-miR-429- CCNA2 exerts pro-oncogenic effects. Conclusion: Overall, our study identified an Exosome-driven ceRNA network in LUAD, and the SNHG6-hsa-miR-429-CHRDL1/CCNA2 axis could be a new therapeutic target for LUAD and our study provides new insights into the molecular mechanisms of LUAD.
Keywords: ceRNAs